PENGARUH PENGGUNAAN E-BOOK MATERI KLASIFIKASI MAKHLUK HIDUP TERHADAP HASIL BELAJAR DAN BERPIKIR KRITIS SISWA SMP - Indrawati Indrawati; Devi Indah Parawansa; Aris Singgih Budiarso (FKIP e-PROCEEDING, 2022)
The use of e-books is a form of utilizing technology-based learning media in an effort to improve student learning outcomes. The purpose of this study was to examine the effect of using the e-book Classification of Living Things on learning outcomes and critical thinking skills of junior high school students. The type of research used is a quasi-experimental research design with a post-test only control group design. The sample of this research was class VII students at MTsN 4 Banyuwangi, which consisted of the experimental class (VII J) and control class (VII I). The data collection technique uses test questions on learning outcomes and critical thinking skills. Data analysis techniques used the normality test, hypothesis testing with the parametric independent sample t-test or the non-parametric Mann-Whitney test. The results showed that the use of e-book material for classification of living things had an effect on the learning outcomes and critical thinking of junior high school students. The appearance of an attractive e-book, can present science material supplemented by pictures and learning videos in one medium, making it easy for students to access learning material, attracting students' attention and making it easier for teachers to deliver subject matter.